2023
DOI: 10.1021/acsanm.3c01543
|View full text |Cite
|
Sign up to set email alerts
|

Thermoplastic Polyurethane/Carbon Nanotube Composites for Stretchable Flexible Pressure Sensors

Abstract: Developing conductive polymer composites (CPCs) with high stretchability and high resistance response is a challenge in the field of flexible sensing. In this study, porous CPCs with a microdome array on the surface are prepared based on thermoplastic polyurethane (TPU) and carbon nanotubes (CNTs). TPU/CNT composites are designed to be strain sensors and pressure sensors capable of monitoring external strain and pressure stimuli. Due to the excellent electrical properties of carbon nanotubes, the synergistic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Furthermore, it has been reported that nanoscale size 1D CNTs feature superior mechanical capabilities, high surface area, and excellent electrical conductivity, which makes them a prospect for fabricating strain sensors. Li et al fabricated a strain sensor by ultrasonically securing CNTs to electrospun TPU fibrous membranes, which demonstrated a large strain response range (600%) but limited sensitivity. Zhou et al prepared an electrospun TPU fibrous membrane decorated with CNTs via spraying and ultrasound-assisted deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been reported that nanoscale size 1D CNTs feature superior mechanical capabilities, high surface area, and excellent electrical conductivity, which makes them a prospect for fabricating strain sensors. Li et al fabricated a strain sensor by ultrasonically securing CNTs to electrospun TPU fibrous membranes, which demonstrated a large strain response range (600%) but limited sensitivity. Zhou et al prepared an electrospun TPU fibrous membrane decorated with CNTs via spraying and ultrasound-assisted deposition.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, elastic materials, such as polydimethylsiloxane (PDMS) [35][36][37][38], silicon rubber (SR) [39,[40][41][42], polyurethane [43], and polyethylene [44], are selected to serve as the substrates of flexible force sensors in the past several years, largely improving the suppleness of the device, establishing conformal attachments to skins or object surfaces. On the other hand, nanomaterials with satisfying conductivity, including carbon black (CB) [44,45] and nanoparticles [46,47], carbon nanotubes (CNTs) [48][49][50], and nanowires (e.g. silver nanowires) [51], two-dimensional graphene and transition metal sulfide [52] come into our mind at the mere mention of conductive materials that utilized in flexible electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…An additional approach to creating conductive sponges is the fabrication of 3D composite sponges through techniques like foaming or freeze-drying, wherein conductive elements are mixed with insulating polymers. [19][20][21][22][23][24] Gongdong et al developed a TPU/CNT porous composite to detect a broad range of objects and high sensitivity using mold transfer and freeze-drying. 19 Xiaoyu et al synthesized PI/CNT composite aerogels for wearable pressure sensors, employing an uncomplicated approach involving freeze drying and thermal imidization techniques.…”
Section: Introductionmentioning
confidence: 99%